Experiences, opportunities and challenges of implementing task shifting in underserved remote settings: the case of Kongwa district, central Tanzania - Munga Michael A; Kilima Stella P; Mutalemwa Prince; Kisoka William J; Malecela Mwelecele N (BMC, 2012)
Abstract Background Tanzania is experiencing acute shortages of Health Workers (HWs), a situation which has forced health managers, especially in the underserved districts, to hastily cope with health workers' shortages by adopting task shifting. This has however been due to limited options for dealing with the crisis of health personnel. There are on-going discussions in the country on whether to scale up task shifting as one of the strategies for addressing health personnel crisis. However, these discussions are not backed up by rigorous scientific evidence. The aim of this paper is two-fold. Firstly, to describe the current situation of implementing task shifting in the context of acute shortages of health workers and, secondly, to provide a descriptive account of the potential opportunities or benefits and the likely challenges which might ensue as a result of implementing task shifting. Methods We employed in-depth interviews with informants at the district level and supplemented the information with additional interviews with informants at the national level. Interviews focussed on the informants' practical experiences of implementing task shifting in their respective health facilities (district level) and their opinions regarding opportunities and challenges which might be associated with implementation of task shifting practices. At the national level, the main focus was on policy issues related to management of health personnel in the context of implementation of task shifting, in addition to seeking their opinions and perceptions regarding opportunities and challenges of implementing task shifting if formally adopted. Results Task shifting has been in practice for many years in Tanzania and has been perceived as an inevitable coping mechanism due to limited options for addressing health personnel shortages in the country. Majority of informants had the concern that quality of services is likely to be affected if appropriate policy infrastructures are not in place before formalising tasks shifting. There was also a perception that implementation of task shifting has ensured access to services especially in underserved remote areas. Professional discontent and challenges related to the management of health personnel policies were also perceived as important issues to consider when implementing task shifting practices. Additional resources for additional training and supervisory tasks were also considered important in the implementation of task shifting in order to make it deliver much the same way as it is for conventional modalities of delivering care. Conclusions Task shifting implementation occurs as an ad hoc coping mechanism to the existing shortages of health workers in many undeserved areas of the country, not just in the study site whose findings are reported in this paper. It is recommended that the most important thing to do now is not to determine whether task shifting is possible or effective but to define the limits of task shifting so as to reach a consensus on where it can have the strongest and most sustainable impact in the delivery of quality health services. Any action towards this end needs to be evidence-based.